Electrical Nerve Stimulation Can Be Used as a Tool in fMRI Studies of Pain- and Tingling-Evoked Activations - Karen D Davis; Chun L Kwan; Adrian P Crawley; David J Mikulis (Pain Research and Management)
OBJECTIVES/HYPOTHESES: To determine whether transcutaneous electrical nerve stimulation (TENS) provides adequate, inexpensive and simple means to image innocuous and pain-related activations in the thalamus and cortex.